THE RESPONSE OF 2nd GRADE “SDN 3 SEKARBANYU” TOWARD CREATIVE READING BOOK (CREBO) MEDIA TO ACHIEVE READING SKILLS FOR LEARNING THEME 7 AND SUB THEMES 2 - Riski Nur Fitrayani; Dwi Kameluh Agustina; Sripit Widiastuti (JOSAR (Journal of Students Academic Research), 2020)
Based on research that has been conducted, researchers found that students in grade 2 at “SDN 3 Sekarbanyu” still not effective when the train reading skills due to lack of media support, the necessary media to attract the attention of students so that the students' reading skills more effectively. The purpose of this research are: (1) describes the development process Crebo media, (2) determine student’s response to media Crebo. The method used in this research is qualitative and quantitative approach. This research was descriptive. The research procedure adapted from Borg and Gall in Sugiono (2013). The results of this research indicate Crebo media assessment of the material aspects of obtaining a mean score of 87.7% to the category of "It's Worth". While aspects of the media get a mean score of 87.8% to the category of "Very Decent" instructional simulation test with respondents 22 students got the results from the aspect of the attractiveness of 92.7% and from 87.2% retention of material aspects. The conclusion of this study is Crebo get a positive response from the respondent and Crebo fit for use as a medium of learning the skills of reading theme 7 and sub themes 2 in 2nd grade